Factors associated with sex work among at-risk female youth in Cambodia: a cross-sectional study. Issue 3 (3rd March 2016) - Brody, Carinne; Tuot, Sovannary; Chhea, Chhorvann; Saphonn, Vonthanak; Yi, Siyan
ABSTRACT: In Cambodia, despite great achievements in reducing the prevalence of HIV in the general population, reducing new HIV infections among young at-risk women remains a challenge. This study was designed to examine the prevalence of risky behaviors of sexually active female youth in Cambodia and to explore risk factors associated with engagement in transactional sex. We surveyed sexually active female youth aged 10–24 enrolled at risk "hotspots" in eight provinces in Cambodia. We collected data on demographic factors, sexual behavior, and factors hypothesized to be associated with transactional sex. Multivariable logistic regression was used to identify associations between demographic and sexual behavior and transactional sex. Of the 280 respondents, the mean age was 21.2, and 48.1% had been paid for sex in the past year. After adjustment, at-risk females who were never have been married (adjusted odds ratio (AOR) 3.40, 95% confidence interval (CI) = 1.65–6.97), have completed less than 6 years of school (AOR 3.26, 95% CI = 1.60–6.66), have 1 or more parents who had died (AOR 4.34, 95% CI = 2.00–9.38), be a heavy alcohol drinker (AOR 3.58, 95% CI = 1.78–7.18), have used a condom with their boyfriend during last sexual encounter (AOR 3.50, 95% CI = 1.68–7.32), and have ever had an HIV test (AOR 3.51, 95% CI = 1.68–7.32) were more likely to engage in sex work. Our findings suggest that prevention strategies for female youth at risk of engagement in sex work should include upstream structural interventions that aim to encourage girls' education and empowerment. In addition, tailored sex education and behavior change messaging about the risks of heavy drinking, condom use with romantic partners, and the importance of frequent HIV testing for at-risk youth and sex workers should be designed and delivered to youth currently engaging in sex work.